The Ironic Sublime - Collins, Tricia; Milazzo, Richard (München : Galerie Albrecht, 1987)
Etkin, Suzan ; Bleckner, Ross ; Cemin, Saint Clair ; Christian, Abraham David ; Fisher, Joel ; Ti Shan Hsu ; McCollum, Allan ; Stephan, Gary ; Otterson, Joel ; Welling, James
The Ironic Sublime, Galerie Albrecht, München, 4.6.1987 - 18.7.1987
boek